DETERMINAN MINAT PEMANFAATAN ULANG PELAYANAN RAWAT JALAN DI PUSKESMAS AIR DINGIN KOTA PADANG - Sri Oktarina (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Decreasing in number of outpatients visiting health care Air Dingin reached 26.33% showed that the patients had their own perception toward the quality which could realize their satisfaction toward received services. Their satisfaction toward received services had effect on interest to reuse the same outpatient service. In order to anticipate tendency of decreasing in number of patient reusing outpatient service, it was needed to conduct a research about determinant factors of patient perception toward service quality with interest to reuse outpatient service at health care Air Dingin Padang city 2017.The type of research was analytical research using cross sectional method. The instrumentation of this research was questionnaire on 79 newcomer patients who receive ambulatory services at health care Air Dingin using accidental sampling. Primary and secondary data were processed and analyzed using chi square test and multivariate using multiple regression logistic test using enter method. Significance was determined with p< 0.05.Based on the result of Univariate analysis showed 53.2% of patients were interested in reuse the services at health care Air Dingin and the variables related to the interest of reusing of health care outpatient services were the patient's perception of the dimensions of reliability, ladder, assurance and direct evidence, together variables which have the greatest influence on interest in reusing outpatient services at health care Air Dingin was the patient's perception of direct evidence dimension.In order to increase the quality, it is recommended health care Air Dingin to conduct andmake repairs of buildings and other infrastructure by cultivating the building facilities for instance waiting room, toilets and mushalla along with complementing the supporting needs to improve the cleanliness of the environment and building of health care.Keywords: Patient Perception, Service Quality, Reuse Outpatient Service Health Care